Korelasi antara Kemampuan Matematika dan Kemampuan Fisika Dasar pada Mahasiswa Program Studi Pendidikan Ilmu Pengetahuan Alam - Aulia Rahmadhani; Meili Yanti (UNIB Press, 2024)
This study aimed to find out the correlation between mathematics and basic physics ability of Natural Science Education Program students. This study was a correlational study that describes the extent to which two or more quantitative variables are interrelated. The study involved 38 students of the Natural Science Education Program, the Faculty of Science and Education, University of West Sulawesi, who programmed compulsory courses in basic physics and mathematics for the odd semester of the academic year 2023/2024. The results of the study were obtained from the physics ability test and the mathematics ability test, which was then, analyzed using the Spearman correlation test. Before the correlations test, the results were tested for normality first using the Shapiro Wilk test. As for the results of the study, the correlation between the mathematics abilities and the basic physics abilities of the students was rs = 0.7675 which is in the category of strong correlations and positive direction. This suggests that when students' mathematics abilities are high then students' basic physics abilities will be high anyway, just as when students’ mathematics abilities are low then students’ basic physics abilities will be low too.